Early mucosal changes in Crohn's disease. Issue 3 (March 1993) - Sankey, E A; Dhillon, A P; Anthony, A; Wakefield, A J; Sim, R; More, L; Hudson, M; Sawyerr, A M; Pounder, R E
Abstract : Aphthoid ulceration has been regarded as an early macroscopic feature of Crohn's disease, yet the cause of this mucosal lesion is unknown. Examination of areas of apparently normal and non-inflamed bowel in Crohn's disease has allowed the identification of mucosal changes which occur before macroscopic and microscopic ulceration. Thirty five resection specimens from patients with Crohn's disease were compared with 12 specimens from patients with ulcerative colitis and 13 controls. Specimens were fixed either by immersion in formalin in the routine way or by perfusion fixation with formalin at mean arterial pressure. Immunostaining for macrophages, vessel wall, and blood constituents allowed identification of small mucosal capillaries which were not apparent otherwise. In Crohn's disease damage and rupture of these small capillaries occurred before infiltration of the lamina propria by inflammatory cells. Loss of the overlying epithelium seemed to follow this vascular damage.